Improvement of Operating Performance of Medium-Speed Marine Diesel Engines Using Marine Diesel Oil with Air Microbubbles - Kawahara, Hideo; Sunada, Tomohiro; Nakatake, Yasuhito; Terasaka, Koichi; Kawahara, Hiroshi; Goto, Hidechika (Testing Center for Oil and Gas LEMIGAS, 2025)
Marine diesel engines are widely adopted as the main auxiliary engines in ships because of their ability to utilize inexpensive heavy fuel oil and their high thermal efficiency per unit engine. This study focuses on practical marine medium-speed diesel engines to investigate the impact of introducing air as fine bubbles into low-sulfur A heavy fuel oil on the operating performance. The results indicated that when fine bubbles were introduced into the fuel, the engine exhibited poor combustion and became unstable at any load when Qa was 0.4 L/min or higher. However, when Qa was below 0.4 L/min, the fuel efficiency improvement increased significantly with increasing load, reaching a maximum reduction of 4.5% at 75% load and Qa = 0.3 L/min. Regarding the exhaust gas characteristics, at low loads, no significant changes were observed in the CO2 and NOx emissions with varying microbubble injection levels. However, at loads of 75% or higher, both the CO2 and NOx emissions decreased as the microbubble injection level increased. Furthermore, introducing fine bubbles into the fuel promoted atomization after fuel injection, similar to the results for heated C heavy oil, leading to improved heat generation rates across the entire engine load range.